Guidelines for Establishing Reliability When Coding Narrative Data. (December 2015) - Syed, Moin; Nelson, Sarah C.
The use of quantitative, qualitative, and mixed methods approaches has been foundational to research on emerging adulthood, yet there remain many unresolved methodological issues pertaining to how to handle qualitative data. The purpose of this article is to review best practices for coding and establishing reliability when working with narrative data. In doing so, we highlight how establishing reliability must be seen as an evolving process, rather than simply a focus on the end product. The review is divided into three broad sections. In the first section, we discuss relatively more quantitatively focused methods of coding and establishing reliability, whereas in the second section we discuss relatively more qualitatively focused methods. In the final section, we provide recommendations for researchers interested in coding narrative and other types of open-ended data. This article is intended to serve as an essential resource for researchers working on a variety of topics related to emerging adulthood and beyond.